Management and outcomes among patients with mixed hepatocholangiocellular carcinoma: A population‐based analysis. Issue 3 (16th December 2018) - Spolverato, Gaya; Bagante, Fabio; Tsilimigras, Diamantis; Ejaz, Aslam; Cloyd, Jordan; Pawlik, Timothy M.
Abstract : Background: We sought to define the management of mixed hepatocellular carcinoma‐intrahepatic cholangiocarcinoma (HCC‐ICC) as well as characterize short‐ and long‐term outcomes of patients with mixed HCC‐ICC. Methods: Patients diagnosed with HCC‐ICC, HCC, or ICC between 2004 and 2015 were identified from the National Cancer Data Base using the International Classification of Diseases for Oncology codes. Short‐ and long‐term outcomes were assessed using univariate and multivariate analyses. Results: Among 174 454 patients, 86.8% had HCC, 12.1% ICC, and 1.1% HCC‐ICC. The incidence of lymphadenectomy was 55.6% among ICC patients vs 15.1% and 34.2% for HCC and HCC‐ICC patients, respectively ( P < 0.001). A 90‐day mortality was comparable among patients with HCC (9.1%), ICC (8.8%), and HCC‐ICC (10.5%) (all P > 0.2). While 42.0% of ICC patients received adjuvant chemotherapy, adjuvant chemotherapy among HCC and HCC‐ICC patients was 13.1% and 27.4%, respectively ( P < 0.001). A 5‐year survival was 43.5% (95% CI, 42.5‐44.5), 33.3% (95% CI, 31.4‐35.3), 34.4% (95% CI, 29.1‐39.8) for HCC, ICC, and HCC‐ICC patients, respectively. Conclusion: Patients who underwent resection of mixed HCC‐ICC had a prognosis that was comparable to ICC, yet worse than HCC. Utilization of lymphadenectomy and adjuvant therapy were low. HCC‐ICC remains a rare disease with a guarded prognosis that should be treated in a multidisciplinary setting.